Principles of formation of the culture of speech of students in the Russian language classes at the university. - Mirzalieva D.S. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The restructuring of the education system in Uzbekistan aims young people to acquire solid knowledge in the name of the country’s prosperity. The youth issue has always been at the center of state policy. The achievement of such great goals as the prosperity of our Motherland, the construction of civil society, economic, spiritual and cultural development, and the rise of the country to the level of developed states depends on how wisely we will accomplish this task.